Class wars between women in Maeve Brennan's 'The Anachronism'. Issue 2 (1st October 2016) - Shumaker, Jeanette
Maeve Brennan's mid-twentieth century stories set in a wealthy village in New York are often read as critiques of prejudice against Irish-American maids. However, in 'The Anachronism' (1954), Maeve Brennan suggests that class, even more than nationality, is central to women's identity in the United States during the 1950s. In this story, Brennan revises stereotypes of class and nationality regarding Irish and English immigrants. Betty, a maid from England, and Mrs. Conroy, an Irish-American widow, forge bonds based on class despite their expected enmity based on nationality.